Malaria vector species in Amazonian Peru co-occur in larval habitats but have distinct larval microbial communities - Prussing, Catharine; Saavedra, Marlon P.; Bickersmith, Sara A.; Alava, Freddy; Guzmán, Mitchel; Manrique, Edgar; Carrasco-Escobar, Gabriel; Moreno, Marta; Gamboa, Dionicia; Vinetz, Joseph M.; Conn, Jan E. (PLOS Neglected Tropical Diseases, 2019)
Author summary The standard methods used to combat mosquitoes that transmit malaria, long-lasting insecticide treated nets and indoor residual spraying, target mosquitoes that bite people indoors and rest indoors after biting. In Amazonian Peru, the major malaria vector, Nyssorhynchus darlingi (formerly Anopheles darlingi), is known to bite and rest mostly outdoors and to feed on animals as well as humans. Therefore, additional methods are needed to control this species, such as targeting immature mosquitoes in water bodies using chemical or biological larvicides or environmental modification. To determine whether this is feasible, more ecological information about Ny. darlingi larval habitats in this region is needed. In this study, we found that Ny. darlingi were more likely to be collected from water bodies in more deforested areas, and in the presence of other species of mosquitoes that transmit malaria. We characterized the bacteria detected in three species of mosquito larvae, and found that the species of mosquito, and not the water body, determined which bacteria were identified. As we found that houses with more malaria cases were located closer to Ny. darlingi larval habitats, management of larval habitats may be an effective method to reduce the risk of malaria in this region.